A modifier-coated wollastonite modified fiber and its preparation method and application

By coating wollastonite modified fibers with modifiers, the problem of insufficient impact performance of existing molding resin composite materials is solved, and the effect of improving interlayer shear force and impact performance is achieved.

CN116163144BActive Publication Date: 2025-04-04JIANGXI GUANGYUAN CHEM +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310084707.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-08
Publication Date
2025-04-04
Estimated Expiration
2043-02-08

AI Technical Summary

Technical Problem

The resin composite materials of existing molding materials have shortcomings in impact properties, mainly because chopped fibers play a role in two-dimensional space, resulting in low interlayer shear force and prone to microcracks.

Method used

The preparation method of wollastonite modified fibers is used to coat wollastonite modified fibers. By immersing the fibers in a calcium silicate sol, calcining and infiltrating the modifier, the modifier-coated wollastonite modified fibers are formed. This method improves the roughness of the fiber and the bonding force with the resin glue, and enhances the interlayer shear force of the molding material.

Benefits of technology

The interlayer shear force and impact performance of the resin composite formed by the molding material after curing is significantly improved, and the overall performance of the resin composite material is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of fiber modification, and provides a modifier-coated wollastonite modified fiber and a preparation method and application thereof. The present invention utilizes calcium silicate sol to infiltrate the fiber, so that calcium silicate whiskers are grown in situ on the fiber surface, which can increase the roughness of the fiber, improve the bonding force of the fiber to the resin glue, and further help to improve the interlaminar shear strength of the resin composite material obtained by curing the molding plastic; when the modifier-coated wollastonite modified fiber is introduced into the molding plastic, the needle-shaped microcrystals of the calcium silicate will extend along the vertical surface of the molding plastic, like tiny pin needles, connecting the layers together, thereby improving the interlaminar shear strength of the resin composite material; the wollastonite modified fiber is then treated with a modifier, and its compatibility with the resin in the molding plastic is greatly improved, which is beneficial to the bonding force between the fiber and the resin, and improves the interlaminar shear of the resin composite material obtained by curing the molding plastic, thereby ensuring the excellent impact performance of the resin composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fiber modification, and in particular to a modifier-coated wollastonite modified fiber and a preparation method and application thereof. Background Art

[0002] Molding compounds are divided into sheet molding compounds and bulk molding compounds. The resin composite materials formed after the molding compounds are cured are widely used as load-bearing structures, such as wind turbine blades, etc. Such load-bearing structures have high requirements on the impact performance of the resin composite materials.

[0003] Existing molding materials are obtained by pressurizing and infiltrating a resin adhesive and a reinforcing material evenly laid on the resin adhesive. The reinforcing material is generally chopped fibers, and the chopped fibers only work in a two-dimensional space, so that the interlaminar shear ratio of the resin composite material formed after curing of this type of molding material is relatively low, and microcracks are easily generated, which leads to low impact performance of the resin composite material. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a modifier-coated wollastonite modified fiber and a preparation method and application thereof. When the modifier-coated wollastonite modified fiber obtained by the preparation method provided by the present invention is used to prepare a molding compound, it can increase the interlaminar shear force of the resin composite material formed after the molding compound is cured, thereby improving the impact performance of the resin composite material.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing modifier-coated wollastonite modified fiber, comprising the following steps:

[0007] The silicate ester and the acid solution are mixed and hydrolyzed to obtain silica sol;

[0008] mixing the silica sol and a soluble calcium salt to obtain a calcium silicate sol;

[0009] impregnating the fiber in the calcium silicate sol to obtain the calcium silicate sol-coated fiber;

[0010] calcining the fiber coated with the calcium silicate sol to obtain wollastonite modified fiber;

[0011] The wollastonite modified fiber is impregnated with a modifier to obtain the modifier-coated wollastonite modified fiber.

[0012] Preferably, the silicate comprises one or more of methyl orthosilicate, ethyl orthosilicate, isopropyl silicate and butyl silicate;

[0013] The acid solution includes hydrochloric acid aqueous solution, sulfuric acid aqueous solution, nitric acid aqueous solution or acetic acid aqueous solution; the mass concentration of the acid solution is 10-30%.

[0014] Preferably, the molar ratio of the silica sol to the soluble calcium salt is 1:1 based on silicate; the silica sol and the soluble calcium salt are mixed at room temperature for 10 minutes to 2 hours.

[0015] Preferably, the fibers include one or more of glass fibers, carbon fibers, aramid fibers and natural fibers; and the impregnation time is 10 to 48 hours.

[0016] Preferably, the calcination temperature is 600-1000° C., and the holding time is 2-5 hours.

[0017] Preferably, the modifier is a lipophilic active agent, and the lipophilic modifier includes one or more of a silane coupling agent, a phthalate coupling agent, organic silicon and stearic acid.

[0018] Preferably, the mass ratio of the wollastonite modified fiber to the modifier is 100:1.5-3; the soaking temperature is 50-80°C, and the soaking time is 3-8h.

[0019] The present invention also provides modifier-coated wollastonite modified fibers obtained by the preparation method described in the above technical solution.

[0020] The present invention provides a molding compound, which is obtained by pressurizing and impregnating a resin adhesive and fibers uniformly laid on the resin adhesive;

[0021] The fiber is the modifier-coated wollastonite modified fiber described in the above technical solution;

[0022] The volume content of the fiber in the molding compound is 30% to 40%;

[0023] The resin glue is a thermosetting resin.

[0024] The present invention also provides a resin composite material, which is obtained by curing the molding compound described in the above technical solution after arranging it layer by layer.

[0025] The invention provides a preparation method of modifier-coated wollastonite modified fiber, comprising the following steps: mixing silicate and acid solution, and hydrolyzing them to obtain silica sol; mixing the silica sol and soluble calcium salt to obtain calcium silicate sol; impregnating fibers in the calcium silicate sol to obtain fibers coated with the calcium silicate sol; calcining the fibers coated with the calcium silicate sol to obtain wollastonite modified fibers; and impregnating the wollastonite modified fibers with a modifier to obtain the modifier-coated wollastonite modified fibers. The present invention utilizes calcium silicate sol to infiltrate fibers, so that calcium silicate whiskers are grown in situ on the fiber surface, thereby increasing the roughness of the fibers and improving the bonding force of the fibers to the resin adhesive, thereby facilitating the improvement of the interlaminar shear strength of the resin composite material obtained by curing the molding plastic. When the modifier-coated wollastonite modified fibers are introduced into the molding plastic, the needle-shaped microcrystals of the calcium silicate extend along the vertical surface of the molding plastic, connecting layers together like tiny pins, thereby improving the interlaminar shear strength of the resin composite material obtained by curing the molding plastic. The wollastonite modified fibers are further treated with the modifier, so that the compatibility with the resin in the molding plastic is greatly improved, which is beneficial to the bonding force of the fibers and the resin, and improves the interlaminar shear of the resin composite material obtained by curing the molding plastic, thereby ensuring the excellent impact performance of the resin composite material.

[0026] The present invention also provides modifier-coated wollastonite modified fibers obtained by the preparation method described in the above technical solution. When the modifier-coated wollastonite modified fibers of the present invention are used in molding materials, the interlaminar shear of the resin composite material obtained by curing the molding materials can be improved, so that the resin composite material has excellent impact performance.

[0027] The present invention also provides a molding compound, which is obtained by pressurizing and impregnating a resin adhesive and fibers uniformly laid on the resin adhesive; the fibers are wollastonite modified fibers coated with a modifier as described in the above technical solution; the volume content of the fibers in the molding compound is 30% to 40%; and the resin adhesive is a thermosetting resin. When the modified fibers of the present invention are used to prepare the molding compound, the resin composite material obtained by curing the molding compound has excellent interlaminar shear force and impact performance.

[0028] The present invention also provides a resin composite material, which is obtained by curing the molding compound described in the above technical solution after layer-by-layer arrangement. The resin composite material provided by the present invention has excellent interlaminar shear force and impact performance. DETAILED DESCRIPTION

[0029] The present invention provides a method for preparing modifier-coated wollastonite modified fiber, comprising the following steps:

[0030] The silicate ester and the acid solution are mixed and hydrolyzed to obtain silica sol;

[0031] mixing the silica sol and a soluble calcium salt to obtain a calcium silicate sol;

[0032] impregnating the fiber in the calcium silicate sol to obtain the calcium silicate sol-coated fiber;

[0033] calcining the fiber coated with the calcium silicate sol to obtain wollastonite modified fiber;

[0034] The wollastonite modified fiber is impregnated with a modifier to obtain the modifier-coated wollastonite modified fiber.

[0035] In the present invention, unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.

[0036] The present invention mixes silicate and acid solution, and performs hydrolysis to obtain silica sol.

[0037] In the present invention, the silicate preferably includes one or more of methyl orthosilicate, ethyl orthosilicate, isopropyl silicate and butyl silicate.

[0038] In the present invention, the acid solution preferably includes hydrochloric acid aqueous solution, sulfuric acid aqueous solution, nitric acid aqueous solution or acetic acid aqueous solution, and more preferably acetic acid aqueous solution. In the present invention, the mass concentration of the acid solution is preferably 10-30%.

[0039] In the present invention, the hydrolysis temperature is preferably room temperature, and the hydrolysis time is preferably 0.5 to 2 hours; the hydrolysis is preferably carried out under stirring, and the stirring speed is preferably 500 to 600 r / min.

[0040] After obtaining the silica sol, the present invention mixes the silica sol with a soluble calcium salt to obtain a calcium silicate sol.

[0041] In the present invention, the soluble calcium salt preferably includes calcium nitrate. In the present invention, the soluble calcium salt is preferably used in the form of a soluble calcium salt aqueous solution, and the concentration of the soluble calcium salt aqueous solution is preferably 100 to 120 mol / L.

[0042] In the present invention, the molar ratio of the silica sol to the soluble calcium salt is preferably 1:1, calculated as silicate.

[0043] In the present invention, when the soluble calcium salt is preferably used in the form of a soluble calcium salt aqueous solution, the silica sol and the soluble calcium salt are preferably mixed in a manner of: adding the soluble calcium salt aqueous solution dropwise into the silica sol.

[0044] In the present invention, the temperature for mixing the silica sol and the soluble calcium salt is preferably room temperature, that is, no additional heating or cooling is required; the time is preferably 10 minutes to 2 hours; the mixing time is preferably started after the soluble calcium salt aqueous solution is added dropwise. In the present invention, the mixing is preferably carried out under stirring.

[0045] After obtaining the calcium silicate sol, the present invention immerses the fiber in the calcium silicate sol to obtain the calcium silicate sol-coated fiber.

[0046] In the present invention, the fiber preferably includes one or more of glass fiber, carbon fiber, aramid fiber and natural fiber. In the present invention, the diameter of the fiber is preferably 1 to 30 μm, and the length of the fiber is preferably 10 to 30 mm.

[0047] In the present invention, the immersion time is preferably 10 to 48 hours. In the present invention, the immersion temperature is preferably room temperature, that is, no additional heating or cooling is required.

[0048] After the impregnation, the present invention preferably further comprises sequentially performing suction filtration and drying. The present invention does not specifically limit the operation of the suction filtration, and the suction filtration parameters well known to those skilled in the art can be used. In the present invention, the drying temperature is preferably 60 to 105°C, more preferably 70 to 100°C; and the drying time is preferably 2 to 5 hours.

[0049] The fiber coated with calcium silicate sol is obtained. The fiber coated with calcium silicate sol is calcined to obtain wollastonite modified fiber.

[0050] In the present invention, the calcination temperature is preferably 600-1000° C., more preferably 700-900° C.; the holding time is preferably 2-5 h, more preferably 3-4 h.

[0051] In the present invention, the calcination can make wollastonite grow needle-shaped crystals on the fiber surface, thereby increasing the specific surface area of ​​the fiber.

[0052] After obtaining the wollastonite modified fiber, the present invention uses a modifier to impregnate the wollastonite modified fiber to obtain the modifier-coated wollastonite modified fiber.

[0053] In the present invention, the modifier is preferably a lipophilic active agent, and the lipophilic modifier preferably includes one or more of a silane coupling agent, a phthalate coupling agent, an organosilicon, and stearic acid, and is further preferably a silane coupling agent or stearic acid. In the present invention, the silane coupling agent preferably includes one or more of vinyl triethoxysilane, vinyl trimethoxysilane, and polyether-modified polydimethylsiloxane.

[0054] In the present invention, the mass ratio of the wollastonite modified fiber to the modifier is preferably 100:1.5-3.

[0055] In the present invention, the soaking temperature is preferably 50 to 80° C., and the soaking time is preferably 3 to 8 hours.

[0056] After the impregnation, the present invention preferably further comprises drying; the drying temperature is preferably 60 to 105° C., and the drying time is preferably 2 to 5 hours.

[0057] In the present invention, during the impregnation process, the modifier is bonded to the wollastonite modified fiber through hydrogen bonding or chemical bonding; and the compounding of the modifier improves the compatibility of the modifier-coated wollastonite modified fiber and the resin, which is beneficial to improve the bonding force between the resin and the fiber and improve the impact strength of the final resin composite material.

[0058] The present invention also provides modifier-coated wollastonite modified fiber obtained by the preparation method described in the above technical solution. In the present invention, the modifier-coated wollastonite modified fiber comprises a fiber body, a wollastonite layer coated on the fiber body, and a modifier layer coated on the wollastonite layer.

[0059] The present invention also provides a molding compound, which is obtained by pressurizing and impregnating a resin adhesive and fibers uniformly laid on the resin adhesive;

[0060] The fiber is the modifier-coated wollastonite modified fiber described in the above technical solution;

[0061] The volume content of the fiber in the molding compound is 30% to 40%;

[0062] The resin glue is a thermosetting resin.

[0063] The molding compound provided by the present invention includes a resin glue. In the present invention, the resin glue is a thermosetting resin; the thermosetting resin preferably includes one or more of unsaturated polyester, polyester resin, epoxy resin and vinyl ester resin. In the present invention, the molding compound preferably includes a sheet molding compound or a block molding compound. When the molding compound is preferably a sheet molding compound, the resin glue is preferably a sheet resin glue; when the molding compound is preferably a block molding compound, the resin glue is preferably a block resin glue.

[0064] The molding compound provided by the present invention comprises fibers uniformly laid on the resin glue, wherein the fibers are the modifier-coated wollastonite modified fibers described in the above technical solution. In the present invention, the volume content of the fibers in the molding compound is preferably 30% to 40%.

[0065] In the present invention, the method for preparing the molding compound preferably comprises the following steps:

[0066] Lay the fibers evenly on the resin glue and impregnate them under pressure.

[0067] The present invention does not specifically limit the operation and parameters of the pressurized infiltration, and the parameters and operations of the pressurized infiltration well known to those skilled in the art may be used.

[0068] The present invention also provides a resin composite material, which is obtained by curing the molding compound described in the above technical solution after arranging it layer by layer.

[0069] The present invention has no requirements on the number of layers of the molding material in the resin composite material, and those skilled in the art can set the number according to actual needs.

[0070] In the present invention, the curing temperature is preferably 20 to 170° C., the pressure is preferably 10 to 20 MPa, and the curing time is preferably 2 to 8 hours.

[0071] The modifier-coated wollastonite modified fiber provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0072] Example 1

[0073] Add 30% glacial acetic acid aqueous solution to ethyl orthosilicate, stir at 600r / min for 0.5h to hydrolyze ethyl orthosilicate to obtain silica sol. Add 100mol / L calcium nitrate aqueous solution dropwise to silica sol (calculated on ethyl orthosilicate, the molar ratio of silica sol to calcium nitrate is 1:1), stir for 10min after adding, and obtain calcium silicate sol; immerse the dried glass fiber (length 30mm) in calcium silicate sol, soak for 10h, filter and put into oven, dry at 70℃ for 5h, and obtain glass fiber coated with calcium silicate sol; then put the glass fiber coated with calcium silicate sol into muffle furnace, calcine at 800℃ for 4h, and obtain wollastonite modified glass fiber.

[0074] Wollastonite modified glass fiber (the mass ratio of wollastonite modified glass fiber to vinyltriethoxysilane is 100:1.5) was impregnated with vinyltriethoxysilane at 50°C for 3 hours and then dried at 80°C for 3 hours to obtain modifier-coated wollastonite modified fiber.

[0075] The obtained modifier-coated wollastonite modified fiber is evenly laid on an unsaturated polyester sheet, and is impregnated under pressure to obtain a sheet molding compound with a thickness of 0.7 mm; wherein: the volume percentage of the modifier-coated wollastonite modified fiber in the sheet molding compound is 35%, the sheet molding compound is cut into a suitable size according to the size of the plate, 3 layers of the sheet molding compound are laid, each layer of the sheet molding compound is flattened with a putty knife to remove bubbles therein, and the compound is cured at 70°C and 10MPa for 120 minutes to obtain a resin composite material with a thickness of 2 mm.

[0076] The impact strength of the obtained resin composite material was measured by GB / T1843-2008 standard and was 19 kJ / m 2 , the impact strength of unmodified SMC (12kJ / m 2 ) increased by 58%.

[0077] Example 2

[0078] Add 30% glacial acetic acid aqueous solution to ethyl orthosilicate, stir at 600r / min for 0.5h to hydrolyze ethyl orthosilicate to obtain silica sol. Add 100mol / L calcium nitrate aqueous solution drop by drop to silica sol (calculated on ethyl orthosilicate, the molar ratio of silica sol to calcium nitrate is 1:1), stir for 10min after adding, and obtain calcium silicate sol; immerse the dried carbon fiber (length 20mm) in calcium silicate sol, soak for 10h, filter and put into oven, dry at 70℃ for 5h, and obtain carbon fiber coated with calcium silicate sol; then put the carbon fiber coated with calcium silicate sol into muffle furnace, calcine at 800℃ for 4h, and obtain wollastonite modified carbon fiber.

[0079] Wollastonite modified carbon fiber (the mass ratio of wollastonite modified carbon fiber and vinyl triethoxysilane is 100:1.5) was impregnated with vinyl trimethoxysilane at 50°C for 3 hours and then dried at 80°C for 3 hours to obtain modifier-coated wollastonite modified fiber.

[0080] The obtained modifier-coated wollastonite modified fiber is evenly laid on an unsaturated polyester sheet, and is impregnated under pressure to obtain a sheet molding compound with a thickness of 0.7 mm; wherein: the volume percentage of the modifier-coated wollastonite modified fiber in the sheet molding compound is 35%, the sheet molding compound is cut into a suitable size according to the size of the plate, 3 layers of the sheet molding compound are laid, each layer of the sheet molding compound is flattened with a putty knife to remove bubbles therein, and the compound is cured at 70°C and 10MPa for 120 minutes to obtain a resin composite material with a thickness of 2 mm.

[0081] The impact strength of the obtained resin composite material was measured by GB / T1843-2008 standard and was 16 kJ / m 2, the impact strength of unmodified SMC (12kJ / m 2 ) increased by 33%.

[0082] Example 3

[0083] Add 30% glacial acetic acid aqueous solution to methyl orthosilicate, stir at 600r / min for 1h to hydrolyze methyl orthosilicate to obtain silica sol. Add 100mol / L calcium nitrate aqueous solution dropwise to silica sol (based on methyl orthosilicate, the molar ratio of silica sol to calcium nitrate is 1:1), stir for 10min after the addition, and obtain calcium silicate sol; immerse the dried glass fiber (length 30mm) in the calcium silicate sol, soak for 10h, filter and put into an oven, dry at 70℃ for 5h, and obtain glass fiber coated with calcium silicate sol; then put the glass fiber coated with calcium silicate sol into a muffle furnace, calcine at 800℃ for 4h, and obtain wollastonite modified glass fiber.

[0084] Wollastonite modified glass fiber (the mass ratio of wollastonite modified glass fiber to polyether modified polydimethylsiloxane is 100:1.5) was impregnated with polyether modified polydimethylsiloxane at 70°C for 4 hours and then dried at 90°C for 3 hours to obtain modifier-coated wollastonite modified fiber.

[0085] The obtained modifier-coated wollastonite modified fiber is evenly laid on the epoxy resin sheet, and is impregnated under pressure to obtain a sheet molding compound with a thickness of 0.7 mm; wherein: the volume percentage of the modifier-coated wollastonite modified fiber in the sheet molding compound is 40%, the sheet molding compound is cut into a suitable size according to the size of the plate, 3 layers of the sheet molding compound are laid, each layer of the sheet molding compound is flattened with a putty knife to remove bubbles, and after curing at 120°C and 15MPa for 2 hours, the temperature is raised to 170°C and the pressure is maintained for curing for 4 hours to obtain a resin composite material with a thickness of 2 mm.

[0086] The impact strength of the obtained resin composite material was measured by GB / T1843-2008 standard and was 20 kJ / m 2 , the impact strength of unmodified SMC (12kJ / m 2 ) increased by 66%.

[0087] Example 4

[0088] Add 30% glacial acetic acid aqueous solution to isopropyl silicate, stir at 600r / min for 1h to hydrolyze isopropyl silicate to obtain silica sol. Add 100mol / L calcium nitrate aqueous solution dropwise to silica sol (based on isopropyl silicate, the molar ratio of silica sol to calcium nitrate is 1:1), stir for 10min after adding, and obtain calcium silicate sol; immerse the dried carbon fiber (length 25mm) in calcium silicate sol, soak for 10h, filter and put into oven, dry at 70℃ for 5h, and obtain carbon fiber coated with calcium silicate sol; then put the carbon fiber coated with calcium silicate sol into muffle furnace, calcine at 800℃ for 4h, and obtain wollastonite modified carbon fiber.

[0089] Wollastonite modified carbon fiber (the mass ratio of wollastonite modified carbon fiber and stearic acid is 100:1.5) was impregnated with stearic acid at 60°C for 4 hours and then dried at 90°C for 2 hours to obtain modifier-coated wollastonite modified fiber.

[0090] The obtained modifier-coated wollastonite modified fiber is evenly laid on the epoxy resin sheet, and is impregnated under pressure to obtain a sheet molding compound with a thickness of 0.7 mm; wherein: the volume percentage of the modifier-coated wollastonite modified fiber in the sheet molding compound is 35%, the sheet molding compound is cut into a suitable size according to the size of the plate, 3 layers of the sheet molding compound are laid, each layer of the sheet molding compound is flattened with a putty knife to remove bubbles, and after curing at 120°C and 15MPa for 2 minutes, the temperature is raised to 170°C, and the curing is continued under pressure for 4 hours to obtain a resin composite material with a thickness of 2 mm.

[0091] The impact strength of the obtained resin composite material was measured by GB / T1843-2008 standard and was 18 kJ / m 2 , the impact strength of unmodified SMC (12kJ / m 2 ) increased by 50%.

[0092] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing modifier-coated wollastonite modified fiber, characterized in that: The following steps are involved: Mixing silicate and acid solution, and hydrolyzing them to obtain silica sol; mixing the silica sol and a soluble calcium salt to obtain a calcium silicate sol; impregnating the fiber in the calcium silicate sol to obtain the calcium silicate sol-coated fiber; calcining the fiber coated with the calcium silicate sol to obtain wollastonite modified fiber; Infiltrating the wollastonite modified fiber with a modifier to obtain the modifier-coated wollastonite modified fiber; The modifier is a lipophilic modifier, and the lipophilic modifier includes one or more of a silane coupling agent, a phthalate coupling agent, organic silicon and stearic acid.

2. The preparation method according to claim 1, characterized in that: The silicate comprises one or more of methyl orthosilicate, ethyl orthosilicate, isopropyl silicate and butyl silicate; The acid solution includes hydrochloric acid aqueous solution, sulfuric acid aqueous solution, nitric acid aqueous solution or acetic acid aqueous solution; the mass concentration of the acid solution is 10-30%.

3. The preparation method according to claim 1, characterized in that: The molar ratio of the silica sol to the soluble calcium salt is 1:1 based on silicate; the silica sol and the soluble calcium salt are mixed at room temperature for 10 minutes to 2 hours.

4. The preparation method according to claim 1, characterized in that: The fibers include one or more of glass fibers, carbon fibers, aramid fibers and natural fibers; and the impregnation time is 10 to 48 hours.

5. The preparation method according to claim 1, characterized in that: The calcination temperature is 600-1000° C., and the heat preservation time is 2-5 hours.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the wollastonite modified fiber to the modifier is 100:1.5-3; the soaking temperature is 50-80°C, and the soaking time is 3-8h.

7. The modifier-coated wollastonite modified fiber obtained by the preparation method according to any one of claims 1 to 6.

8. A molding compound, characterized in that: It is obtained by impregnating resin glue and fibers uniformly laid on the resin glue under pressure; The fiber is the modifier-coated wollastonite modified fiber as claimed in claim 7; The volume content of the fiber in the molding compound is 30% to 40%; The resin glue is a thermosetting resin.

9. A resin composite material, characterized in that: The resin composite material is obtained by curing the molding compound described in claim 8 after layer-by-layer arrangement.

Citation Information

Patent Citations

  • Method for preparing modified acicular wollastonite

    CN101774594A

  • Modifier, modified wollastonite modified by modifier, and preparation method and application of modified wollastonite

    CN112646395A

  • Boron nitride heterogeneous filler and preparation method thereof, and fiber-reinforced epoxy resin heat-conducting composite material, preparation method and application thereof

    CN112876741A